Influence of Gas Type on Reactive Species Formation, Antimicrobial Activity, and Cytotoxicity of Plasma-Activated Water Produced in a Coaxial DBD Reactor - Miranda, F. S. [UNESP]; Tavares, V. K.F. [UNESP]; Silva, D. M. [UNESP]; Milhan, N. V.M. [UNESP]; Neto, N. F. Azevedo; Gomes, M. P.; Pessoa, R. S.; Koga-Ito, C. Y. [UNESP] (Springer Nature, 2024)
In this study, a coaxial dielectric barrier discharge (DBD) reactor was employed using various gases: compressed air (CA), helium (He), or argon (Ar) to produce plasma-activated water (PAW) from deionized water. The influence of these gases on the generation and quantification of reactive oxygen and nitrogen species (RONS) was examined. Their impact on PAW's physicochemical properties, including pH, oxygen reduction potential (ORP), and conductivity, was also assessed. In parallel, the efficacy of produced PAW against microbial species such as Staphylococcus aureus, Escherichia coli, and Candida albicans was evaluated, in addition to their cytotoxicity to mammalian cells. Notably, after a 10-min contact, a 99.99% reduction in S. aureus and E. coli was observed when CA and Ar were used, and reductions of 99.96% and 99.95% were seen when He was employed, respectively. For C. albicans, reductions of 12.05% with CA, 22.89% with Ar, and 39.76% with He was observed. After 30 min, a reduction of up to 53.41% was achieved with Ar. Additionally, PAW generated with all the gases were classified as non-cytotoxic. These findings underscore the potential of the coaxial DBD reactor system in PAW production, emphasizing its significant antimicrobial properties and low toxicity to mammalian cells.
Keywords: Antimicrobial; Cytotoxicity; Dielectric barrier discharge; Plasma-activated water; Reactive oxygen and nitrogen species